1992
DOI: 10.1104/pp.100.3.1326
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of sym-17

Abstract: R82 (sym-1 7), a stable mutant of Pisum sativum L. cv Sparkle, is described. The shoot growth of the mutant was less than that of its parent under light or dark growth conditions. Gibberellic acid treatment did not normalize the shoot growth of R82. The mutant had thick and short roots. It formed few nodules, but the specific nitrogenase activity was not affected. R82 produced and contained more ethylene than Sparkle. It also contained more free 1-aminocyclopropane-1-carboxylic acid than did its parent in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…Using the properties of ACC and AVG and altering their levels, Oldroyd et al (2001) were able to modulate the infection frequency and the number of nodules formed on barrel medic; whereas ACC lowers frequency and nodule number, AVG increases them. These results confirmed the findings of Peters and Crist-Estes (1989), Fearn and LaRue (1991), Lee and LaRue (1992a), and Guinel and LaRue (1992) who showed that treating wild-type seedlings with ethylene inhibitors or antagonists consistently, although not always significantly, increased nodule number. Neither of these compounds, however, affected nodulation on soybean (Lee and LaRue 1992c).…”
Section: Use Of Chemical Compounds Involved In and (Or) Interacting Wsupporting
confidence: 81%
See 1 more Smart Citation
“…Using the properties of ACC and AVG and altering their levels, Oldroyd et al (2001) were able to modulate the infection frequency and the number of nodules formed on barrel medic; whereas ACC lowers frequency and nodule number, AVG increases them. These results confirmed the findings of Peters and Crist-Estes (1989), Fearn and LaRue (1991), Lee and LaRue (1992a), and Guinel and LaRue (1992) who showed that treating wild-type seedlings with ethylene inhibitors or antagonists consistently, although not always significantly, increased nodule number. Neither of these compounds, however, affected nodulation on soybean (Lee and LaRue 1992c).…”
Section: Use Of Chemical Compounds Involved In and (Or) Interacting Wsupporting
confidence: 81%
“…One pea mutant, sym17, is known to be an ethylene overproducer (Lee and LaRue 1992a). This mutant is characterized by short stature and abnormal root growth; furthermore, it has pronounced apical dominance and wrinkled pods.…”
Section: Use Of Mutants and Transgenic Plantsmentioning
confidence: 99%
“…Also, treatment with the ethylene synthesis inhibitor AVG did not rescue the root architectural defects in the mutant. In contrast, the previously isolated mutants of P. sativum, sym5, which is an ethylene hypersensitive mutant (Fearn and LaRue, 1991b), or sym17 and sym16, which are ethylene overproduction mutants (Lee and LaRue, 1992;Guinel and Sloetjes, 2000), displayed a nodulation phenotype rescued by AVG addition. Taken together, these results implied that BRUSH exerts an ethylene-independent function.…”
Section: The Brush Phenotype Differs From That Of Previously Describementioning
confidence: 60%
“…We have previously described brz, a mutant gene in Sparkle that causes leaf necrosis and excessive iron uptake as well as decreased nodulation (Kneen et al 1990b). In chickpea, a nonnodulating mutant also has wrinkled pods (Davis et al 1986), as does syml7 (Lee and LaRue 1992). It is possible that all the pleiotropic effects are produced by mutations tightly linked to the sym loci rather than direct effects of the sym mutations.…”
Section: Discussionmentioning
confidence: 99%